Laser laparoscopic, cholecystectomy - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 1990)
In the “traditional” removal of a diseased gallbladder (cholecystectomy), the required main incision (a right upper quadrant incision) requires that the patient, because of the pain associated, not move or breathe deeply after the procedure. This could complicate the recovery process ifinfection or respiratory problems become evident.